Fundamental Factor Analysis On Banking Stock Price In LQ45 - Idah Zuhroh; Alvio Veronika (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study analyzes the influence of fundamental factors (inflation, exchange rates, ROA, ROE, and BOPO) on the LQ 45 Banking Stock Price. The research subjects are banks listed in LQ 45 for the quarterly period 2015-2019, using Panel Data Regression. The analysis model is the Common Effect Model (CEM). This study uses 2 models where the first model tests all variables except ROE, and the second model tests all variables except ROA. The results showed that the inflation and exchange rate variables significantly affect the LQ45 Banking Stock Price. On the other hand, the variables of ROA, ROE, and BOPO did not significantly affect the LQ45 banking financial stock price. The research results simultaneously showed that in model 1, the variables of inflation, exchange rate, ROA, and BOPO significantly affect the LQ45 banking stock price. Whereas in model 2, jointly, the variables of inflation, exchange rate, ROE, and BOPO significantly affect the LQ45 banking stock price.